Decreasing number of distance shooting in handball - trend of nowadays male handball competition - Smolarczyk, M. (Biomedical Human Kinetics, 2023)
Study aim: The aim of this study was to analyze and compare performance data structure in two consecutive EHF Men`s EURO competition in 2020 and 2022 in order to highline significance of differences in two-year cycle of European Championships.